The enchanted years of the stage Kansas City at the crossroads of American theater, 1870-1930 - Londré, Felicia Hardison, 1941- (University of Missouri Press, 2007)
"Drawing on the recollections of renowned theater critic David Austin Latchaw and on newspaper archives of the era, Londre chronicles the "first golden age" of Kansas City theater, from the opening of the Coates Opera House in 1870 through the gradual decline of touring productions after World War I"--Provided by publisher.